PENGARUH KUALITAS PRODUK, PENETAPAN HARGA, DAN PELAKSANAAN PROMOSI TERHADAP KEPUASAN KONSUMEN PRODUK AYAM ORGANIK PT ELHA NARITA PERKASA (Studi Pada Konsumen O’Chicken Pekanbaru) - Muhammad Roberto Gunawan; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Consumer satisfaction is one of the most important factors in the marketing concept, this is the background of this research. Good product quality, appropriate pricing, and proper promotion in front of consumers are the most important factors supporting consumer satisfaction. This strategy is implemented by PT Elha Narita Perkasa O'Chicken Pekanbaru Branch. This study aims to determine the effect of product quality, pricing, and implementation of promotions on consumer satisfaction of PT Elha Narita Perkasa's organic chicken products (Study on Consumers of O'Chicken Pekanbaru). The method used in this research is descriptive and quantitative, with data sources from primary data and secondary data. The analytical method used in this research is simple and multiple linear regression analysis, and through validity and reliability tests. In this study the results obtained are Product Quality (X1) has a positive and significant effect on Consumer Satisfaction (Y), Pricing (X2) has a positive and significant effect on Consumer Satisfaction (Y), Promotion Implementation (X3) has a positive and significant effect on Consumer Satisfaction (Y), and Product Quality (X1), Pricing (X2), and Promotion Implementation (X3) have a positive and significant effect on Consumer Satisfaction (Y) at PT Elha Narita Perkasa O'Chicken Pekanbaru Branch. Keywords: Product Quality, Pricing, Promotion Implementation, and Consumer Satisfaction.PENDAHULUAN